A large-scale database study for the prescription status of a new voltage-gated Ca2+ channel α2δ ligand, mirogabalin, in Japan. (22nd January 2022) - Ushida, Takahiro; Yokoyama, Mizuka; Shiosakai, Kazuhito; Saito, Kengo; Ibe, Shigehisa; Okuizumi, Kaoru
ABSTRACT: Background: A new voltage-gated Ca 2+ channel α2 δ ligand, mirogabalin, was first approved for treating peripheral neuropathic pain in Japan in 2019. This is the first report on the prescription status of mirogabalin using a large-scale prescription database. Research Design and Methods: The authors analyzed the prescription data of 12, 924 patients prescribed mirogabalin between 1 June and 31 August 2020. The endpoints were the number of patients prescribed, prescription days, prescription doses, dose changes, co-prescription patterns, medication possession ratio (MPR), and treatment discontinuation rates (TDRs). Results: Mirogabalin was newly prescribed to 7, 914 patients in the 3-month study period. Most patients were prescribed mirogabalin at about 10 mg/day during the study period, and 30.9% of patients were prescribed ≥ 20 mg/day on Day 90 after the first prescription. The most frequently prescribed concomitant drug was celecoxib. The MPR (80 to 110%) was 86.2%, indicating good treatment adherence. The cumulative TDRs during ≤ 7 Days, Days 31–60, and 61–90 were 14.0%, 70.0%, and 77.9%, respectively. Conclusions: Mirogabalin was prescribed to a considerable number of patients. These results may be useful for optimizing mirogabalin use for patients with peripheral neuropathic pain in daily clinical practice. Clinical trial registration number: UMIN000042592